Carolinian-English Dictionary - Jackson, Frederick H. (University of Hawai'i Press, 2023)
Carolinian is a member of the Trukic subgroup of the Micronesian group of Oceanic languages. This is the first English dictionary of the three Carolinian dialects spoken by descendants of voyagers who migrated from atolls in the Central Caroline Islands to Saipan in the Northern Mariana Islands. This dictionary provides English definitions for almost 7,000 Carolinian entries and an English-Carolinian finder list. A special effort was made to include culturally important words, particularly those related to sailing, fishing, cooking, house building, traditional religion, and family structure. With this work, the compilers also establish an acceptable standard writing system with which to record the Carolinian language.